Encapsulation of Bovine Primordial Follicles in Rigid Alginate Does Not Affect Growth Dynamics - Kathryn L. McElhinney; Erin E. Rowell; Monica M. Laronda (Bioengineering, 2024)
The only fertility preservation and subsequent restoration option for many patients facing gonadotoxic treatments is ovarian tissue cryopreservation and transplantation. While this process is successful for some, there is significant room for improvement to extend the life of the transplant and to make it safe for patients that may have metastatic disease within their ovarian tissue. We need a deeper understanding of how the physical properties of the ovarian microenvironment may affect folliculogenesis to engineer an environment that supports isolated follicles and maintains primordial follicle quiescence. Bovine ovaries were used here as a monovulatory model of folliculogenesis to examine the effects of primordial follicle activation and growth under different physical conditions. We found that there were no differences in activation, growth or survival when primordial follicles were cultured in isolation or in situ (remaining in the tissue) under two significantly differently rigid alginate gels. To determine if the extra rigid environment did not affect activation in isolated follicles due to an immediate activation event, we used 5-ethynyl-2′-deoxyuridine (EdU) to track follicle activation during the isolation process. We identified EdU incorporation in granulosa cells after primordial follicles were isolated from the surrounding extracellular matrix (ECM). These findings support that isolation of primordial follicles from the ECM is an activating event and that the differentially rigid environments assessed here had no effect on follicle growth. Further work is needed to suppress activation in primordial follicles to maintain the ovarian reserve and extend the life of an ovarian tissue transplant.